2012
DOI: 10.3390/rs4040849
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Net Primary Production of Turfgrass in an Urban-Suburban Landscape with QuickBird Imagery

Abstract: Vegetation is a basic component of urban-suburban environments with significant area coverage. As a major vegetation type in US cities, urban turfgrass provides a range of important ecological services. This study examined the biological carbon fixation of turfgrass in a typical residential neighborhood by linking ground-based measurements, high resolution satellite remote sensing, and ecological modeling. The spatial distribution of turfgrass and its vegetative conditions were mapped with QuickBird satellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Figure 2, for example, compares the spectral signature of turfgrass species in treatment I, measured at two different distances from the sprinklers and averaged for all measurement dates. The spectral signature at the closest distance was similar to that presented in [5]. At this location, 38% of the incident radiation in NIR waveband was reflected on average, an indication of large number of hydrated cell walls and air cavities in the mesophyll tissue of turf blades.…”
Section: Spectral Characteristics Of Turfgrasssupporting
confidence: 55%
See 1 more Smart Citation
“…Figure 2, for example, compares the spectral signature of turfgrass species in treatment I, measured at two different distances from the sprinklers and averaged for all measurement dates. The spectral signature at the closest distance was similar to that presented in [5]. At this location, 38% of the incident radiation in NIR waveband was reflected on average, an indication of large number of hydrated cell walls and air cavities in the mesophyll tissue of turf blades.…”
Section: Spectral Characteristics Of Turfgrasssupporting
confidence: 55%
“…Hence, improving landscape irrigation management is necessary to foster sustainable management of urban water resources in the western USA [4]. Turfgrass has been the focus of irrigation studies during the past few decades, as it is one of the most dominant components of urban landscapes [5]. Carrow [6] categorized the methods for identifying the appropriate timing of turfgrass irrigation into three groups: (i) based on soil moisture depletion; (ii) based on climatic data and reference evapotranspiration; and, (iii) using canopy characteristics such as temperature and visible signs of stress.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SOI was detected more accurately than SOG, probably due to the less varied spectral characteristics of SOI compared with those of SOG [5]. We found that the spectral reflectance of SOG changed with the objects that cast shadows, especially in the NIR band, while that of SOI remained largely unchanged.…”
Section: Discussionmentioning
confidence: 64%
“…The four multispectral bands of QuickBird data were simulated with the appropriate CROPSCAN bands as weighted averages [5]. The band widths of the spectroradiometer vary from 6.8 nm to 12 nm in the visible and from 11 nm to 13 nm in the near infrared.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation